William Webb’s Contrarian Thesis: A Book Review of “The End of Telecoms History” - Holmes, Jim (Journal of Telecommunications and the Digital Economy, 2024)
William Webb’s new book, The End of Telecom’s History, argues that 5G has failed to deliver on its promises and, further, that this is largely because increased data rates and data capacity are approaching sufficiency in the developed world. Thus, the basis of the 5G business case has not materialised. In this book, Web draws an analogy with the end of history generally, meaning the resolution of challenges that have defined an epoch. The implications of his thesis, in terms of industry investment and structure, and the impacts on all stakeholders, are set out. Webb’s conclusions are contentious, and there are many in the industry who challenge his basic arguments. Some of the responses are mentioned in this review.